PSYCHOLOGICAL IMPACT OF SPATIAL CYBERTEXT ENVIRONMENTS ON SOCIAL MEDIA PLATFORMS: A PRAGMATIC PERSPECTIVE ON PSYCHOLINGUISTICS STUDENTS - Wahyudi Rahmat; Nor Hazwani Munirah Lateh; Yohan Kurniawan (LLDIKTI Wilayah X, 2025)
The rapid evolution of digital communication has transformed linguistic interaction into a spatially distributed phenomenon, wherein meaning emerges through multimodal cues embedded in virtual environments. This study examines the psychological implications of spatial cybertext environments, interactive, hypertextual spaces within social media, on psycholinguistics students who navigate these platforms as both users and analysts of language. Grounded in pragmatic and psycholinguistic frameworks, this research employs a qualitative descriptive approach to explore how spatial discourse structures, multimodal symbols, and digital affordances shape users’ cognitive and emotional engagement. Data were collected from in-depth interviews, participant observations, and online discourse samples drawn from academic social media interactions. The findings indicate that students’ exposure to spatial cybertexts leads to three distinct psychological phenomena: (1) cognitive tension due to multimodal overload and fragmented attention; (2) pragmatic drift arising from context ambiguity and algorithmic mediation; and (3) metapragmatic awareness, reflecting a heightened sensitivity to language use, politeness, and identity performance in digital contexts. The study concludes that pragmatic awareness functions as both a cognitive and emotional regulator, enabling psycholinguistics students to sustain interpretive coherence amid digital overstimulation. The research offers insights into how spatial discourse in social media environments redefines the relationship between language, cognition, and affect in contemporary digital learning.